THE STRATEGIC MARITIME CANALS AND STRAITS (Perner's Contacts, 2016)
Maritime canals and straits play a relevant role in sea transport; they shorten navigation time in transport of cargoes between sea ports and contribute to reduce transport costs. They have passed though the reconstruction and modernisation to adapt the present requirements of maritime transport because of the increase of the volume of cargoes that is transported by this mode of transport.